Optimizing Crew Feedback Systems for Proactive Experience Management in Air Travel - Maida Nkonye Asata; Daphine Nyangoma; Chinelo Harriet Okolo (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In the highly competitive airline industry, delivering consistently exceptional passenger experiences is paramount to building brand loyalty and operational excellence. Crew members, as frontline service providers, hold critical insights into inflight service dynamics and passenger needs. This examines the optimization of crew feedback systems as a strategic tool for proactive experience management in air travel. By facilitating timely, accurate, and actionable feedback from cabin crew, airlines can identify service gaps early, implement targeted interventions, and enhance overall service quality. The research explores existing feedback mechanisms, including digital platforms, surveys, and debriefing sessions, highlighting challenges such as underreporting and delayed responses. Technological innovations such as mobile applications, AI-driven sentiment analysis, and integrated analytics dashboards are evaluated for their potential to transform feedback into predictive insights. Organizational factors, including fostering a culture that values feedback and empowering crew members with the necessary training and incentives, are also discussed. Case studies from leading airlines demonstrate measurable improvements in passenger satisfaction and operational efficiency following the implementation of optimized feedback systems. Challenges such as data privacy concerns and resistance to change are acknowledged, with recommendations for overcoming these barriers through transparent communication and continuous system refinement. This concludes that optimizing crew feedback systems is instrumental in shifting from reactive to proactive experience management, enabling airlines to anticipate passenger needs, swiftly address service disruptions, and maintain competitive advantage. Future research directions include longitudinal assessments of feedback system impact and the integration of emerging technologies to further enhance real-time responsiveness and personalization in passenger service.